2018
DOI: 10.3390/ijerph15112600
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the Nonsteroidal Anti-Inflammatory Drug Piroxicam by Iron Activated Persulfate: The Role of Water Matrix and Ultrasound Synergy

Abstract: This work examined the oxidation of Piroxicam (PIR), a representative nonsteroidal anti-inflammatory drug using iron activated persulfate. The effect of persulfate dosing was vital for the efficiency of the process. The addition of 20 mg/L sodium persulfate (SPS) eliminated 500 μg/L of PIR in less than 20 min at natural pH. PIR decomposition followed pseudo-first-order kinetics, and the observed kinetic constant increased by 2.1 times when the initial concentration of PIR decreased from 2000 to 250 μg/L. Acidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 50 publications
3
8
0
Order By: Relevance
“…However, the observed kinetic constant decreased approximately 14 times, i.e., from 0.55 to 0.04 min −1 from ultrapure to secondary effluent. The same behavior was observed in the case of iron-activated persulfate [30], where in the presence of organics the kinetic constant decreased from 0.15 to 0.07 min −1 . Recently, Ioannidi et al [31] demonstrated that even UV-A light could activate persulfate and degrade the endocrine disruptor propyl paraben.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…However, the observed kinetic constant decreased approximately 14 times, i.e., from 0.55 to 0.04 min −1 from ultrapure to secondary effluent. The same behavior was observed in the case of iron-activated persulfate [30], where in the presence of organics the kinetic constant decreased from 0.15 to 0.07 min −1 . Recently, Ioannidi et al [31] demonstrated that even UV-A light could activate persulfate and degrade the endocrine disruptor propyl paraben.…”
Section: Introductionsupporting
confidence: 77%
“…A similar behavior was observed by Outsiou et al [53], where the addition of more than 50 mg/L chloride increased the removal of bisphenol A using SPS activated by a bimetallic carbon xerogel catalyst. On the contrary, the presence of chloride did not have any particular effect on the destruction of piroxicam using iron-activated persulfate [30]. However, the effect of chloride needs further investigation as several studies have linked its presence to the formation of organochlorine compounds that are potentially carcinogenic [52].…”
Section: Effect Of Water Matrixmentioning
confidence: 93%
See 2 more Smart Citations
“…Due to such limitations, new alternatives are being sought in order to overcome the inefficiency of conventional techniques for removal or degradation of dyes. Advanced oxidative processes (AOPs) have demonstrated great efficiency in degrading recalcitrant organic pollutants [5,6,7,8,9,10,11,12]. Among AOPs, those based on Fenton reactions are considered promising for dye degradation [13].…”
Section: Introductionmentioning
confidence: 99%